Carbon nanotube/polyurethane modified hollow fiber‐pencil graphite electrode for in situ concentration and electrochemical quantification of anticancer drugs Capecitabine and Erlotinib - Es'haghi, Zarrin; Moeinpour, Fatemeh (Engineering in life sciences, 2019)
A sensitive electrochemical sensor has been designed for in situ preconcentration and determination of anticancer drugs Capecitabine (CPT) and Erlotinib hydrochloride (ETHC) based on a pencil graphite electrode modified with multivalued carbon nanotube—polyurethane (MWCNT‐PUFIX) nanocomposite that was supported with a piece of polypropylene hollow fiber (HF‐PGE). The electrochemical behavior of CPT and ETHC on the MWCNT‐PUFIX/HF‐PGE modified electrode was investigated by differential pulse voltammetry (DPV) techniques and the obtained results confirmed its efficiency for sensing of CPT and ETHC. The synthesized nanocomposite was characterized by infrared spectroscopy and scanning electron microscope. After optimization of some effective parameters on the method efficiency including pH, nanocomposite amount, the type of organic solvent, scan rate and the effect of some additives, the mentioned sensor presented suitable results for determination of CPT and ETHC with the linear ranges from 7.70 to 142.00 μM and 0.11 to 23.50 μM and detection limits of 0.11 and 0.02 μM, respectively. Also, the fabricated sensor has shown good performance in analysis of CPT and ETHC in biological samples.